Association between estradiol levels in early pregnancy and risk of preeclampsia after frozen embryo transfer - Hsieh, Yun-Chiao; Kao, Tzu-Ching; Yang, Ih-Jane; Yang, Po-Kai; Chao, Kuang-Han; Chen, Mei-Jou; Yang, Jehn-Hsiahn; Chen, Shee-Uan (Frontiers in Endocrinology, 2023)
Introduction The failure of remodeling the spiral arteries is associated with the pathogenesis of preeclampsia. Estradiol (E2) plays a crucial role in placentation and may be involved in the development of preeclampsia. However, there is a lack of data in this area. This study aims to assess the association between serum estradiol levels in early pregnancy and the risk of preeclampsia. Methods We conducted a retrospective cohort study on patients who conceived after frozen embryo transfer (FET) using data from a database at a university-affiliated in vitro fertilization center. The study period spanned from January 1, 2010, to December 31, 2020. Multivariable logistic regression analyses were performed to determine the adjusted effect of E2 levels on the risk of preeclampsia. We compared the odds ratios of preeclampsia across quartiles of E2 levels and assessed their significance. Results Serum E2 levels at the fifth gestational week were significantly different between women with and without preeclampsia after FET programmed cycles (607.5 ± 245.4 vs. 545.6 ± 294.4 pg/ml, p=0.009). A multivariable logistic regression model demonstrated that E2 levels in early pregnancy were independent risk factors for preeclampsia. We observed an increased odds ratio of preeclampsia with increasing quartiles of estradiol levels after adjusting for potential confounders in FET programmed cycles. When comparing quartiles 3 and 4 (E2 > 493 pg/ml at the fifth gestational week) to quartiles 1 and 2, the odds ratios of preeclampsia were significantly higher. Conclusion We found that serum E2 levels in early pregnancy may impact the risk of preeclampsia, particularly following FET programmed cycles. The association between E2 levels in early pregnancy and preeclampsia deserves further investigation.